Inhibition of Cathepsin S in Autoimmune CD25KO Mouse Improves Sjögren Disease–Like Lacrimal Gland Pathology - Scholand, Kaitlin K. (2024)
Purpose: CD25KO mice are a model of Sjögren disease (SjD) driven by autoreactive T cells. Cathepsin S (CTSS) is a protease crucial for major histocompatibility complex class II presentation that primes T cells. We investigated if a diet containing CTSS inhibitor would improve autoimmune signs in CD25KO mice.Methods: Four-week female CD25KO mice were randomly chosen to receive chow containing a CTSS inhibitor (R05461111, 262.5 mg/kg chow) or standard chow for 4 weeks. Cornea sensitivity was measured. Inflammatory score was assessed in lacrimal gland (LG) histologic sections. Flow cytometry of LG and ocular draining lymph nodes (dLNs) investigated expression of Th1 and Th17 cells. Expression of inflammatory, T- and B-cell, and apoptotic markers in the LG were assessed with quantitative PCR. The life span of mice receiving CTSS inhibitor or standard chow was compared. CD4+ T cells from both groups were isolated from spleens and adoptively transferred into RAG1KO female recipients.Results: Mice receiving CTSS inhibitor had better cornea sensitivity and improved LG inflammatory scores. There was a significant decrease in the frequency of CD4+ immune cells and a significant increase in the frequency of CD8+ immune cells in the dLNs of CTSS inhibitor mice. There was a significant decrease in Th1 and Th17 cells in CTSS inhibitor mice in both LGs and dLNs. Ifng, Ciita, and Casp8 mRNA in CTSS inhibitor mice decreased. Mice that received the CTSS inhibitor lived 30% longer. Adoptive transfer recipients with CTSS inhibitor-treated CD4+ T cells had improved cornea sensitivity and lower inflammation scores.Conclusions: Inhibiting CTSS could be a potential venue for the treatment of SjD in the eye and LG.